2001
DOI: 10.1128/mcb.21.4.1228-1238.2001
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP F Influences Binding of a 64-Kilodalton Subunit of Cleavage Stimulation Factor to mRNA Precursors in Mouse B Cells

Abstract: Previous studies on the regulation of polyadenylation of the immunoglobulin (Ig) heavy-chain pre-mRNA argued for trans-acting modifiers of the cleavage-polyadenylation reaction operating differentially during B-cell developmental stages. Using four complementary approaches, we demonstrate that a change in the level of hnRNP F is an important determinant in the regulated use of alternative polyadenylation sites between memory and plasma stage B cells. First, by Western analyses of cellular proteins, the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 49 publications
6
148
0
1
Order By: Relevance
“…Th ese results indicate that hnRNP F may act as a potent repressor of TERRA levels. Th is repression might be linked to the known role of hnRNP F as a negative regulator of pre-mRNA cleavage, which is needed for the polyadenylation steps 27 . In particular, hnRNP F downregulation may result in increased polyA + -TERRA contributing to augmented protection of 3 ′ end of TERRA from exonucleases, which in turn could increase TERRA stability and the observed increase in TERRA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Th ese results indicate that hnRNP F may act as a potent repressor of TERRA levels. Th is repression might be linked to the known role of hnRNP F as a negative regulator of pre-mRNA cleavage, which is needed for the polyadenylation steps 27 . In particular, hnRNP F downregulation may result in increased polyA + -TERRA contributing to augmented protection of 3 ′ end of TERRA from exonucleases, which in turn could increase TERRA stability and the observed increase in TERRA levels.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, affinity of CstF for the U͞GU-rich elements, which are highly variable in sequence, defines the efficiency of poly(A) sites by determining the stability of the cleavage complex on the pre-mRNA (22). In mammalian cells, several studies have correlated shifts in the choice of poly(A) sites with quantitative or qualitative variations of CstF-64 (23)(24)(25)(26)(27). In Drosophila, we and others have shown that modulation of su(f) activity in su(f) mutants affects the utilization of alternative poly(A) sites in the f 1 mutation, the Adh͞Adhr locus, and the su(f) gene itself (19,20,28,29).…”
mentioning
confidence: 99%
“…Nascent RNA cleavage in polyadenylation can be blocked by U1A (Phillips, Pachikara et al 2004;Ma, Gunderson et al 2006) or hnRNP F (Veraldi, Arhin et al 2001); the levels of both of these are high in B-cells and lower in plasma cells (summarized in Table 1) and (Ma, Gunderson et al 2006) consistent with a loss of their inhibitory function on the poly(A) sites in plasma cells. While hnRNP F might be expected to block any poly(A) site based on its sequence preference for downstream regions (Alkan, Martincic et al 2006), we found by a micro-array analyses of hnRNP F transfected cells that only some genes were affected, most notable among these were secretory Igh and ELL2, a transcription elongation factor (Martincic, Alkan et al 2009).…”
Section: Alterations In Trans-acting Factors For Polyadenylation In Bmentioning
confidence: 91%
“…A shift in the SR-proteins is seen from the activating type (ASF/SF2) in B-cells to the repression type (SRp20) in plasma cells. The factors hnRNP F and U1A, both of which block the secretory-specific poly(A) site from functioning, are reduced in plasma cells (Veraldi, Arhin et al 2001;Milcarek, Martincic et al 2003;Alkan, Martincic et al 2006) and (Ma, Gunderson et al 2006) which would allow the secretory site to function better. The major effectors in the alternative processing in B versus plasma cells are summarized in Table 1.…”
Section: Differential Expression Of Factors In a Number Of Pathways Smentioning
confidence: 99%